An Exploratory Study on the Relationship between Parents' Passion for Sport/Exercise and Children's Self- and Task-Perceptions in Sport/Exercise. Issue 3 (June 2014) - Chen, Chen-Yueh
This study investigated the relationship between parents' passion fo r sport/exercise and children's self- and task-perceptions in sport and exercise. Paired samples of 312 children, 312 fathers, and 312 mothers were collected using two-stage sampling; parents were classified based on their passion for sport and exercise as high concordance if both parents had a high passion for sport and exercise, low concordance if neither parent had a passion for sport and exercise, or discordant. Intrinsic interest value, attainment value/importance, extrinsic utility value, ability/expectancy, task difficulty, and required effort were measured, as well as harmonious and obsessive passion. Children's self- and task-perceptions in sport and exercise were examined with respect to parents' passion for sport and exercise. The results of the study indicated that children of parents with high concordance in harmonious passion for sport and exercise scored higher on intrinsic interest value, attainment value/importance, extrinsic utility value, ability / expectancy, task difficulty, and required effort in sport and exercise than counterparts with discordant and low concordance parents. Similar patterns were found for obsessive passion in parents.